2010
DOI: 10.1089/jop.2009.0073
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy With or Without Intravitreal Triamcinolone Acetonide for Symptomatic Polypoidal Choroidal Vasculopathy

Abstract: PDT reduced the risks of visual loss in patients with symptomatic PCV in the short term but the effect might not be sustained after 1 year. The adjunctive use of IVTA during PDT did not appear to result in additional benefit for treating PCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Subretinal and vitreous hemorrhage and, to a lesser extent, secondary CNV appear to be the most commonly reported adverse events in patients treated with verteporfin PDT. 55,58,61,71,73,78,80,83,95,106,108,135 Level I safety data for verteporfin PDT and ranibizumab in PCV are consistent with their established safety profiles in neovascular AMD. 30,165,166 In recent studies of verteporfin as monotherapy 167 In cases where CNV coexists with PCV or where a differential diagnosis is difficult, combination therapy would ensure that the standard of care is met for both conditions.…”
Section: Direct Thermal Laser Photocoagulation Still Hassupporting
confidence: 54%
See 2 more Smart Citations
“…Subretinal and vitreous hemorrhage and, to a lesser extent, secondary CNV appear to be the most commonly reported adverse events in patients treated with verteporfin PDT. 55,58,61,71,73,78,80,83,95,106,108,135 Level I safety data for verteporfin PDT and ranibizumab in PCV are consistent with their established safety profiles in neovascular AMD. 30,165,166 In recent studies of verteporfin as monotherapy 167 In cases where CNV coexists with PCV or where a differential diagnosis is difficult, combination therapy would ensure that the standard of care is met for both conditions.…”
Section: Direct Thermal Laser Photocoagulation Still Hassupporting
confidence: 54%
“…30,175,178 Polypoidal choroidal vasculopathy is a chronic, recurrent condition: the need for retreatment with verteporfin PDT or ranibizumab in some patients, especially with longer-term follow-up, is well documented. 30,[55][56][57][58]61,62,66,69,[71][72][73]78,86,89,[91][92][93]126 The recommendations of the panel for monitoring are consistent with the methodology of the majority of the studies retrieved in the literature search on PCV.…”
Section: Direct Thermal Laser Photocoagulation Still Hasmentioning
confidence: 57%
See 1 more Smart Citation
“…Thus, inflammation may be a key element in the pathophysiology of PCV. Previous studies have shown that PDT combined with intravitreal injection of triamcinolone acetonide or STTA leads to improved visual acuity and lowers the rate of retreatment 20. This may be associated with inhibitory effects of triamcinolone acetonide for inflammation at the choriocapillaris caused by irradiated laser beam.…”
Section: Discussionmentioning
confidence: 99%
“…(135) Another retrospective study which compared PDT monotherapy to combination PDT and intravitreal bevacizumab and triamcinolone acetonide, found better visual acuity outcomes and longer treatment-free periods with combination therapy. (136) A study by Sakai and colleagues compared outcomes in patients receiving PDT and intravitreal bevacizumab with or without sub-tenon’s kenalog, found a larger percentage of patients with vision improvement and longer treatment-free periods in the group receiving sub-tenon’s kenalog.…”
Section: Management Of Pcvmentioning
confidence: 99%